On Subject Inversion In Proto-Bantu Relative Clauses - Hamlaoui, Fatima (My University, 2022)
This chapter concentrates on the canonical position of lexical subjects in Proto-Bantu non-subject relative clauses. Based on both the geographical and the genealogical distribution of different word orders (Subject Verb-only, Verb Subject-only and Subject Verb / Verb Subject), I propose that the Verb Subject (VS) order is an innovation that came into use only after the split between the North-Western Cameroonian branch of Grollemund et al.’s (2015) classification and the rest of the tree, that is, node 2 or 3. I thus argue for a revision of Meeussen’s (1967) and Nsuka-Nkutsi’s (1982) claim that Proto-Bantu (node 1) non-subject relative clauses were characterised by a VS order. After expanding Nsuka-Nkutsi’s sample from over a hundred Narrow Bantu languages to a total of 167 languages (151 Narrow Bantu and 16 other Niger-Congo languages), we observe that VS-only is still the most frequent word order. However, the Subject Verb (SV) order is dominant in the major clades of Grollemund et al. (2015) located in the north-western Bantu area (20 out of 22 languages in our sample), that is, in the languages that are both closer to the Bantu homeland and more similar to the Niger-Congo languages outside of Narrow Bantu in our sample. SV-only is also found in a significant portion of our sample in the Eastern branch (28 out of 57 languages). Together, these facts suggest that the SV order might be more ancient than previously thought. If this scenario is correct, Bantu zone A languages would not have lost VS due to their evolution from more syntheticity to more analyticity, but they would never have had it at all.
Keywords: Proto-Bantu; Relative Clauses; Subject inversion